VD_FINDINFO HC / 2014 / 224 vom 30. Januar 2014 - VD Tribunal cantonal (2014)
RÉSILIATION IMMÉDIATE, RÉPRIMANDE, TRAVAILLEUR, DANS L'ACCOMPLISSEMENT DU TRAVAIL | 337 al. 1 CO, 337 al. 2 CO, 337 al. 3 CO, 337 CO